2014
DOI: 10.3390/s140509153
|View full text |Cite
|
Sign up to set email alerts
|

Surveying Wearable Human Assistive Technology for Life and Safety Critical Applications: Standards, Challenges and Opportunities

Abstract: In this survey a new application paradigm life and safety for critical operations and missions using wearable Wireless Body Area Networks (WBANs) technology is introduced. This paradigm has a vast scope of applications, including disaster management, worker safety in harsh environments such as roadside and building workers, mobile health monitoring, ambient assisted living and many more. It is often the case that during the critical operations and the target conditions, the existing infrastructure is either ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(90 citation statements)
references
References 99 publications
(128 reference statements)
0
90
0
Order By: Relevance
“…According to the study as focused in [8] [11], theoretically Wi-Fi consumes 100mW-1000mW energy at the data rate 10Mbps-100Mbps, communication range is between 10-100 meters, network lifetime is few hours to 5 days. Bluetooth consumes 2.5mW-100mW energy at the data rate 1Mbps-10Mbps, communication range is between 1-10 meters, network lifetime is 1-7 days.…”
Section: Existing Communication Technologies For Outer-wban and Theirmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the study as focused in [8] [11], theoretically Wi-Fi consumes 100mW-1000mW energy at the data rate 10Mbps-100Mbps, communication range is between 10-100 meters, network lifetime is few hours to 5 days. Bluetooth consumes 2.5mW-100mW energy at the data rate 1Mbps-10Mbps, communication range is between 1-10 meters, network lifetime is 1-7 days.…”
Section: Existing Communication Technologies For Outer-wban and Theirmentioning
confidence: 99%
“…Indeed, if patients monitoring and medical care can be performed wirelessly, the patient is no longer constrained in his movements thus reducing the mortality rate. It is notable that, the mortality rate during Hajj is higher due to certain noncommunicable health hazards [1] [7][8].…”
Section: Introductionmentioning
confidence: 99%
“…IoH is the concept of connecting, monitoring and recording human data with the Internet. Wearable technology is revolutionizing many applications, including health-care, sports and fitness, rescue and emergency management, augmented reality, fashion, and so on [1]. Recently, wearable technology revenue has greatly increased, passing from USD 2 billion in 2013 to more than USD 15 billion in 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Elderly people can also be remotely monitored and followed up. For instance, it was recently reported that the UK National Health Service (NHS) could save up to 7 billion pounds per year by using innovative technologies to deliver quality health-care to chronically ill with fewer hospital visits and admissions [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…The second deployment method is wearing BMSs, whereby BMSs are attached to the skin or sewn onto a patient's shirt. They externally monitor organ conditions, including temperature, blood pressure, and heartbeat [3]. In the third method, BMSs are deployed near the patient's body to monitor body positions, including sleep duration, arm direction, and handshaking [4].…”
Section: Introductionmentioning
confidence: 99%